Human Gait During Level Walking With an Occupational Whole-Body Powered Exoskeleton: Not Yet a Walk in the Park - Kim, Sunwook; Srinivasan, Divya; Nussbaum, Maury A.; Leonessa, Alexander (IEEE access, 2021)
With rapid advancements in exoskeleton technologies, a whole-body powered exoskeleton (WB-PEXO) for augmenting human physical capacity (a "super-operator") is generating increasing attention as an integral part of Industry 4.0. Our understanding of WB-PEXO use is lagging, however, largely due to the lack of detailed evaluations via human-subjects testing of a WB-PEXO. We examined (independently from the manufacturer of a WB-PEXO) the potential impacts of using a state-of-the-art WB-PEXO prototype (pre-alpha prototype version of the Sarcos Guardian ® XO ® ) on users ( n=5 ) during a common basic activity in the workplace, level walking. With emphasis on the "human", impacts of XO use (compared to a no EXO baseline) were assessed in terms of lower limb intersegmental coordination, muscle activity, and postural dynamic stability. A larger variance between participants was observed for intersegmental coordination with XO use, and participants appeared to rely on more hip motions. When using the XO, participants exhibited higher muscle activity levels in the lower limb muscle groups monitored. Further, there was a moderate to high similarity in muscle activity profiles between the XO and no EXO conditions ( R_{XY}\left ({τ }\right)=0.70-0.92) , yet muscle activity profiles when using the XO were generally time-lagged from those without the XO. We discuss the results within the context of developing a mental model for walking with the XO, and aspects of human-robot interaction such as transparency of the XO and understanding user state and intention. In concluding, we outline several future research topics for occupational WB-PEXO development.